Evaluation of Patients With Cognitive Impairment Due to Suspected Idiopathic Normal-Pressure Hydrocephalus at Medical Centers for Dementia: A Nationwide Hospital-Based Survey in Japan - Kazui, Hiroaki; Hashimoto, Mamoru; Takeda, Shigetoshi; Chiba, Yasuji; Goto, Tokiko; Fuchino, Katsuhiro (Frontiers in Neurology, 2022)
Objective: Treatment of idiopathic normal-pressure hydrocephalus (iNPH) requires collaboration between dementia specialists and neurosurgeons. The role of dementia specialists is to differentiate patients with iNPH from patients with other dementia diseases and to determine if other dementia diseases are comorbid with iNPH. We conducted a nationwide hospital-based questionnaire survey on iNPH in medical centers for dementia (MCDs). Methods: We developed a questionnaire to assess how physicians in MCDs evaluate and treat patients with cognitive impairment due to suspected iNPH and the difficulties these physicians experience in the evaluation and treatment of patients. The questionnaire was sent to all 456 MCDs in Japan. Results: Questionnaires from 279 MCDs were returned to us (response rate: 61.2%). Patients underwent cognitive tests, evaluation of the triad symptoms of iNPH, and morphological neuroimaging examinations in 96.8%, 77.8%, and 98.2% of the MCDs, respectively. Patients with suspected iNPH were referred to other hospitals (e.g., hospitals with neurosurgery departments) from 78.9% of MCDs, and cerebrospinal fluid (CSF) tap test was performed in 44 MCDs (15.8%). iNPH guidelines (iNPHGLs) and disproportionately enlarged subarachnoid space hydrocephalus (DESH), a specific morphological finding, were used and known in 39.4% and 38% of MCDs, respectively. Logistic regression analysis with “Refer the patient to other hospitals (e.g., hospitals with neurosurgery departments) when iNPH is suspected.” as the response variable and (a) using the iNPHGLs, (b) knowledge of DESH, (c) confidence regarding DESH, (d) difficulty with performing brain magnetic resonance imaging, (e) knowledge of the methods of CSF tap test, (f) absence of physician who can perform lumbar puncture, and (g) experience of being told by neurosurgeons that referred patients are not indicated for shunt surgery as explanatory variables revealed that the last two factors are significant predictors of patient referral from MCDs to other hospitals. Conclusions: Sufficient differential or comorbid diagnosis using CSF tap test is performed in a few MCDs. Medical care for patients with iNPH in MCDs may be improved by having dementia specialists perform CSF tap tests and share the eligibility criteria for shunt surgery with neurosurgeons.